2017
DOI: 10.1111/itor.12371
|View full text |Cite
|
Sign up to set email alerts
|

The influence of reference effect on pricing strategies in revenue management settings

Abstract: This paper studies the reference effect on dynamic pricing in revenue management for cases with limited capacity and stochastic demand. We first present a single-period fixed pricing (FP) model in finite horizon with fixed capacity and stochastic demand, and show that there is a unique optimal solution. The model is then extended to a discrete-time dynamic pricing (DP) model as a benchmark case. We subsequently propose a DP model with reference effect (DPR), investigate the properties of the revenue function, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 36 publications
0
15
0
Order By: Relevance
“…Lin [25] considered the price promotion in a supply chain when taking into account the reference price effects and showed that the reference price effects could mitigate double marginalization effects. Yang et al [51] studied dynamic pricing strategies with reference effect for a seller facing a classical revenue management problem with stochastic demand, finite horizon, and fixed capacity.…”
Section: Shichen Zhang Jianxiong Zhang Jiang Shen and Wansheng Tangmentioning
confidence: 99%
“…Lin [25] considered the price promotion in a supply chain when taking into account the reference price effects and showed that the reference price effects could mitigate double marginalization effects. Yang et al [51] studied dynamic pricing strategies with reference effect for a seller facing a classical revenue management problem with stochastic demand, finite horizon, and fixed capacity.…”
Section: Shichen Zhang Jianxiong Zhang Jiang Shen and Wansheng Tangmentioning
confidence: 99%
“…Within this literature track, various issues have been studied including, for example, right capacity and the conditions under which rationing is optimal (Liu and van Ryzin, 2008); the sufficient condition for optimal capacity rationing when customers have bounded rational expectations (Huang and Liu, 2015); and the pricing policy and rationing level of a firm in markup and markdown scenarios (Liu and Shum, 2013). Compared to this vast literature (other examples include Li et al, 2015;Bajwa et al, 2016;Duan et al, 2016;Yang et al, 2017;Yu et al, 2017;Feng, 2018Feng, , 2019, we focus on the supplier-induced scarcity initiated during the introductory period, and its impact on both consumers' preferences and pricing policies.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Considering market demand disruptions and the reference effect on consumer purchasing decisions, Yang et al. () investigate how a firm facing limited capacity and stochastic demand should dynamically set optimal prices in the presence of reference effect scenarios. By developing and comparing three pricing models, a single‐period fixed pricing ( FP ) model, a discrete‐time dynamic pricing ( DP ) model, and a DP model with reference effect ( DPR ), they explore the properties of the optimal pricing strategies for these models and investigate the relationships between the maximum expected revenue, the initial stock, and the remaining selling horizon.…”
Section: Using Information To Deal With Disruptionsmentioning
confidence: 99%